A Silver Nanocluster Containing Interstitial Sulfur and Unprecedented Chemical Bonds. (1st August 2018) - Liu, Xu; Chen, Jishi; Yuan, Jinyun; Li, Yizhi; Li, Jin; Zhou, Shiming; Yao, Chuanhao; Liao, Lingwen; Zhuang, Shengli; Zhao, Yan; Deng, Haiteng; Yang, Jinlong; et al.
Abstract: The emergence of thiolated metal nanoclusters provides opportunities to identify significant and unprecedented phenomena because they are at quantum sizes and can be characterized with X‐ray crystallography. Recently silver nanoclusters have received extensive interest owing to their merits, such as low‐cost and rich properties. Herein, a thiolated silver nanocluster [Ag46 S7 (SPhMe2 )24 ]NO3 (Ag46 for short) with a face‐centered cubic (fcc) structure was successfully synthesized and structurally resolved by X‐ray analysis. Most importantly, interstitial sulfur was found in the lattice void of Ag46 without lattice distortion or expansion, indicating that the classic theory of interstitial metal solid solutions might be not applicable at quantum size. Furthermore, unprecedented chemical bonds and unique structural features (such as asymmetrically coordinated μ4 ‐S) were found in Ag46 and might be related to the interstitial sulfur, which is supported by natural population analyses.